A randomised controlled trial of the effect of displayed pain score on analgesic administration in adult trauma patients at the emergency department of Kuala Lumpur Hospital - Cecilia, Anthonysamy (2008)
Pain is a common symptom experienced by trawna patients presenting to emergency departments. Yet only 38% of patients evaluated for major trawna received analgesic (Silka eta/., 2004). The management of pain is often regarded as less important compared to arriving at diagnosis and treatment proper. Yet a physician's primary duty is to comfort, manage and reduce the suffering of a patient. Documentation of patient's pain score at triage has been recommended by JCAHO as a tool towards improving pain management in the ED . STUDY OBJECTIVE The objective of this study was to determine the effect of documentation and display of patients' self assessment of pain using numerical rating scale (NRS) on analgesic use among adult trauma patients at the emergency department af Kuala Lumpur Hospital. XV METHOD A randomized control trial was conducted recruiting 200 trauma patients who presented to the secondary triage and treated in the green zone of the emergency department in Kuala Lumpur Hospital. Only patients who had GCS of 15/15 were included. Convenient sampling was used. Pain score was done using NRS for all patients. They were randomized to have the pain score either displayed prominently in the trial group or not displayed in the control. Outcome measured were proportion of patients receiving analgesic and timing from triage to analgesic administration. RESULTS The mean pain score was 5. 7. 15 % of patients had mild pain, 48 % had moderate pain and 37% had severe pain. 26.5% (53) patients received analgesics. There was no significant difference in the proportion of patients, 29.7 % receiving analgesic when pain score was displayed, compared to 23.2 % when pain score was not displayed. p value was 0.3 by chi-square test. Within the trial group, the severity of pain was significantly associated with receiving analgesic (p = 0.007). Severity of pain did not have a confounder effect on the association of displayed pain score and analgesic administration. Mean time to receiving analgesic from triage was 81.3 minutes in the trial sample compared to 88. 7 minutes in the control sample. There was no relationship between pain score and the timing to analgesic.